The Efficacy and Biocompatibility of Hydroxyapatite Composites Impregnated with Vancomycin as a Local Drug Delivery System - Klabklay, MD, P; Oungbho, Ph.D, K; Tangtrakulwanich, MD, Ph.D, B (Journal of Southeast Asian Orthopaedics, 2022)
Objective: This study investigated the efficacy and biocompatibility of local biodegradable composites composed of hydroxyapatite, plaster of Paris, and binders (chitosan or alginate) impregnated with vancomycin. Material and Method: Local biodegradable tablet composed of hydroxyapatite, plaster of Paris, and binders (chitosan or alginate) were prepared and mixed with vancomycin. The tablet was tested for releasing profile using dissolution apparatus for 1 week. Biocompatibility of each composite was tested using MTT test. Results: Vancomycin could be released from the composite from both using binder either chitosan or alginate for at least one week but the release profile of the composite using alginate showed a better pattern of elution than those using chitosan. Biocompatibility test against osteoblast demonstrated good biocompatibility of the both composites at different concentration of drug use comparing to the control group. Conclusion: The local hydroxyapatite composite composed of hydroxyapatite, plaster of Paris and binder either chitosan or alginate seems to be a promising local biodegradable delivery system for vancomycin in treating of methicillin-resistant Staphylococcus aureus osteomyelitis.